Hidden Obesity in Dialysis Patients: Clinical Implications. Issue 5 (4th May 2016) - Abramowitz, Matthew K.; Sharma, Deep; Folkert, Vaughn W.
Abstract: While body‐mass index (BMI) is used to diagnose obesity in the general population, its application in the end‐stage renal disease (ESRD) population is fraught with difficulty. A major limitation is its inability to distinguish muscle mass from fat mass, thereby leading to misclassification of individuals with poor muscle mass but excess adipose tissue as non‐obese (i.e. BMI <30 kg/m 2 ). As muscle wasting is common among ESRD patients, this is an important problem. A substantial proportion of ESRD patients have levels of BMI in the normal range, yet excess adiposity based on other measures. The importance of this "hidden" obesity remains to be determined, but it must be recognized in order for obesity interventions to be appropriately targeted and tested in the ESRD population.